Genetic algorithm optimized network in cloud data centre - Nurika, O. (American Scientific Publishers, 2016)
In this paper, we look into an area where a cloud network can be optimized. Past studies showed that the unoptimized network device is a main factor behind interruptions in a cloud network. However, network device optimization in a cloud network has never been done according to our review. Hence, we propose a methodology to optimize the usage of network devices, by simultaneously optimizing the configurations of these devices. The optimization revolves around the combinations of network card parameters configurations. This could be considered a combinatorial problem, which in our methodology is attempted to be solved using genetic algorithm. The generated network card configurations adapt to the typical characteristics of cloud network traffic pattern. Experiments via simulation were conducted using our validated mathematical models. The results of the experiments show the effectiveness of our proposed methodology to enhance network speed in the cloud data centre. Â© 2016 American Scientific Publishers. All rights reserved.